Phenotypic Heterogeneity of Familial Hypertriglyceridemia: A Case Series of a Mother and Three Siblings with Diverse Clinical Outcomes - Anak Agung Ngurah Adhipa Prasada; Cyndiana Widia Dewi Sinardja (PT BMW Journal Sejahtera, 2026)
Background: Familial hypertriglyceridemia (FHTG) is a common autosomal dominant lipid disorder characterized by elevated plasma triglycerides (TG). According to the AHA/ACC 2018 and ESC/EAS 2019 guidelines, TG levels are classified as borderline high (150–199 mg/dL), high (200–499 mg/dL), severe (500–999 mg/dL), or very severe (≥1000 mg/dL). Its clinical expression is highly variable even within the same family, influenced by secondary factors including diet, obesity, diabetes, alcohol intake, and medications. Case Description: We present a case series of four family members — a 63-year-old mother (proband) and her three children aged 28, 33, and 41 years — all exhibiting hypertriglyceridemia with markedly different TG levels (118–1061 mg/dL), comorbidity burden, and clinical outcomes. Target TG levels for therapy are <150 mg/dL (normal), or <500 mg/dL as an urgent target to prevent acute pancreatitis in patients with severe hypertriglyceridemia. All family members are currently managed with fenofibrate, with variable degrees of TG control: the mother has achieved the therapeutic target (<150 mg/dL), the first daughter and brother demonstrate persistent elevation above target despite pharmacotherapy, and the youngest daughter exhibits persistent severe hypertriglyceridemia despite pharmacotherapy (TG 1061 mg/dL, far exceeding the ≥1000 mg/dL very-severe threshold). Discussion: This family illustrates the remarkable phenotypic heterogeneity of FHTG. The proband has achieved good TG control despite significant cardiovascular comorbidities, while the youngest sibling presented with persistent severe hypertriglyceridemia complicated by pregnancy, necessitating substitution of fenofibrate with omega-3 fatty acids and lifestyle modification. The 33-year-old male sibling developed premature cardiovascular disease (microvascular dysfunction) and type 2 diabetes mellitus (T2DM) at a young age, underscoring the metabolic risks associated with persistent severe hypertriglyceridemia despite pharmacotherapy. Analysis of extended family lipid profiles — including LDL-cholesterol, HbA1c, HDL-cholesterol, and uric acid — further reveals the spectrum of atherogenic dyslipidemia within these kindred. Conclusion: Cascade screening of first-degree relatives of patients with FHTG is critical, with particular urgency in Asian populations given distinct dietary patterns and genetic predispositions to hypertriglyceridemia. Management must be individualized, particularly in special populations such as pregnant women. This case series highlights the necessity of long-term, family-centered approaches to lipid management.